Assessment of Biomass Feedstock Availability and Bio-Refinery Sites Selection for Cellulosic Ethanol and Bio-Methane Production (Case Study: Palm Oil Processing Waste as Bio-Refinery Feedstock in East Kalimantan , Indonesia) - Andriana, Yusuf (LIPI Press, 2014)
This study discussed about feedstock availability and bio-refinery sites selection for palm-oil-processingwaste- to-bio-energy industry. A case study was based on existing palm oil millings in East Kalimantan province.The objectives of this research were (1) to assess the availability of palm oil processing waste as feedstock of bio-refinery turning into palm-oil-processing-waste-to-bio-energy industry in East Kalimantan and (2) to select bio-refinery sites in East Kalimantan. Time series analysis was used to assess feedstock availability of palm oil processing waste and Analytical Hierarchy Process (AHP) was used to select bio-refinery sites in East Kalimantan. The result of this research showed that the availability volumes of palm oil waste as raw material for bio-refinery at palm oil processing industry were predicted as many as 2,645,736 tons of empty fruit bunches, 1,814,238 tons palm oil fiber, 806,328 tons palm kernel shell, and 7,345,144 tons palm oil milling effluent in 2022. The appropriate bio-refinery sites for palm-oil-processing-waste-to-bio-energy industry in East Kalimantan based on experts judgment using Analytical Hierarchy Process was Kutai Kartanegara Regency.